COMPARATIVE ANALYSIS OF STRATEGIES OF PRICING AND PROMOTION OF PRODUCTS AND SERVICES ON NETWORK VALUES MARKET - Viktor E. Dementiev; Sergey G. Evsukov; Elena V. Ustyuzhanina (Вестник Российского экономического университета имени Г. В. Плеханова)
The article studies conditions of dynamic pricing and marketing policy efficiency on network values market in circumstances of temporary supplier’s monopoly. The research method is economic-mathematic modeling of value cost dependence on the number of its consumers and demand for the value on price. By computer tests possibilities to use dynamic pricing for resolving three objectives are analyzed, they are maximization of net integral discounted profit of network value supplier; minimization of time necessary to reach the project repayment and minimization of time necessary to reach the maximum integral profit. The authors come to the conclusion about the importance of taking into account the peculiarities of network values markets for developing business marketing policy. They substantiate the expediency of using policy of network values differentiation (free provision of simple version of values and sale of extended version) in order to motivate net shaping and to speed up the achievement of project repayment. The economic-mathematic model of shaping network values market was put forward, which differs from existing analogues by more accurate reflection of specific rise in customer cost and shaping demand for these values. The model was used to get answers to two questions: which strategies of pricing can provide better indicators of project quality and whether it is reasonable to motivate demand by providing a free simplified version of value.